Computing : a Historical and Technical Perspective. - Igarashi, Yoshihide (Taylor and Francis, 2014)
Exploring a vast array of topics related to computation, Computing: A Historical and Technical Perspective covers the historical and technical foundation of ancient and modern-day computing. The book starts with the earliest references to counting by humans, introduces various number systems, and discusses mathematics in early civilizations. It guides readers all the way through the latest advances in computer science, such as the design and analysis of computer algorithms. Through historical accounts, brief technical explanations, and examples, the book answers a host of questions, including:W.